Eksistensi Dewan Pengupahan Dalam Proses Penetapan Upah Minimum - Anas Santoso; Asri Wijayanti (Wijayakusuma Law Review, 2020)
Abstract An existence of Wage Council in the process of setting minimum wages is currently less than optimal. This research aimed to analyze the existence of Wage Councils in the process of setting minimum wages based on an analysis of substance and procedures in legislation. This research was a normative juridical with statute approach. The results showed that the differences in the implementation of the provisions of Article 88 paragraph (4) of Law 13/2003 with the implementing regulations contained in Article 43 paragraph (1) PP 78/2015 jo Keppres 107/2004 jo Article 1 Permenaker 15/2018. The resulting recommendation made a revision of the rule of law that can optimize the Wage Council's performance in the process of setting minimum wages.Keywords:  Minimum Wage; Wage Council; Openness. AbstrakEksistensi Dewan Pengupahan dalam proses penetapan upah minimum, saat ini kurang maksimal. Penelitian ini bertujuan untuk menganalisis eksistensi Dewan Pengupahan dalam proses penetapan upah minimum berdasarkan analisis substransi dan prosedur yang ada dalam peraturan perundang-undangan. Penelitian ini adalah yuridis normatif dengan statute approach. Hasil dari penelitian ini adalah adanya perbedaan implementasi ketentuan Pasal 88 ayat (4) UU 13/2003 dengan peraturan pelaksananya  yang terdapat pada Pasal 43 ayat (1) PP 78/2015 jo Keppres 107/2004 jo Pasal 1 Permenaker 15/2018.  Rekomendasi yang dihasilkan adalah dibuatkan revisi aturan hukum yang dapat mengoptimalkan kinerja Dewan Pengupahan dalam proses penetapan upah minimum.Kata Kunci : upah minimum; Dewan Pengupahan; keterbukaan.